Impact of unacceptable behaviour between healthcare workers on clinical performance and patient outcomes: a systematic review. Issue 9 (19th January 2022) - Guo, Linda; Ryan, Benjamin; Leditschke, Isabel Anne; Haines, Kimberley J; Cook, Katrina; Eriksson, Lars; Olusanya, Olusegun; Selak, Tanya; Shekar, Kiran; Ramanan, Mahesh
Abstract : Background: Recent studies suggest that displays of unacceptable behaviour, including bullying, discrimination and harassment, between healthcare workers (HCWs) may impair job performance, and in turn, increase the frequency of medical errors, adverse events and healthcare-related complications. The objective of this systematic review was to summarise the current evidence of the impact of unacceptable behaviour occurring between HCWs on clinical performance and patient outcomes. Methods: We searched MEDLINE, Embase, PsycINFO and CINAHL from 1 January 1990 to 31 March 2021. The search results were screened by two independent reviewers and studies were included if they were original research that assessed the effects of unacceptable behaviour on clinical performance, quality of care, workplace productivity or patient outcomes. Risk of bias was assessed using tools relevant to the study design and the data were synthesised without meta-analysis. Results: From the 2559 screened studies, 36 studies were included: 22 survey-based studies, 4 qualitative studies, 3 mixed-methods studies, 4 simulation-based randomised controlled trials (RCTs) and 3 other study designs. Most survey-based studies were low quality and demonstrated that HCWs perceived a relationship between unacceptable behaviour and worse clinical performance and patient outcomes. This was supported by a smaller number of higher quality retrospective studies and RCTs. Two of four RCTs produced negative results, possibly reflecting inadequate power or study design limitations. No study demonstrated any beneficial effect of unacceptable behaviour on the study outcomes. Conclusions: Despite the mixed quality of evidence and some inconsistencies in the strengths of associations reported, the overall weight of evidence shows that unacceptable behaviour negatively affects the clinical performance of HCWs, quality of care, workplace productivity and patient outcomes. Future research should focus on the evaluation and implementation of interventions that reduce the frequency of these behaviours.